1999
DOI: 10.1074/jbc.274.40.28371
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin and Platelet-derived Growth Factor Induce Association of Endogenous Focal Adhesion Kinase with Src in Intact Swiss 3T3 Cells

Abstract: Stimulation of quiescent Swiss 3T3 cells with bombesin induces a rapid increase in the formation of complexes between focal adhesion kinase (FAK) and Src family members, which can be extracted with a buffer containing Triton, deoxycholate, and SDS but not with a buffer containing Triton alone. An increase in complex formation between FAK and Src in response to bombesin could be detected within 1 min, reached a maximum after 10 min, and declined toward base-line levels after 60 min of bombesin treatment. Bradyk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 84 publications
10
80
1
1
Order By: Relevance
“…Our results also differ with PYK2 from the effect of transforming growth factor-␤ in mammary cells where only two sites were tyrosine-phosphorylated (pY402 and pY881) (39). However, our results showing tyrosine phosphorylation in all three sites in FAK by CCK A receptor activation are similar to the effects of cannabinoids in hippocampal cells (48), bombesin in 3T3 cells (53), thrombin in platelets (6), and fibronectin in fibroblasts (42). Similarly, stimulation of tyrosine phosphorylation of all three sites of PYK2 is seen with endothelin-1 in mesangial cells (45), thrombin or histamine in HUVEC cells (43,46), as well as the effect of transforming growth factor-␤ in mammary epithelial cells (39).…”
Section: Resultscontrasting
confidence: 93%
“…Our results also differ with PYK2 from the effect of transforming growth factor-␤ in mammary cells where only two sites were tyrosine-phosphorylated (pY402 and pY881) (39). However, our results showing tyrosine phosphorylation in all three sites in FAK by CCK A receptor activation are similar to the effects of cannabinoids in hippocampal cells (48), bombesin in 3T3 cells (53), thrombin in platelets (6), and fibronectin in fibroblasts (42). Similarly, stimulation of tyrosine phosphorylation of all three sites of PYK2 is seen with endothelin-1 in mesangial cells (45), thrombin or histamine in HUVEC cells (43,46), as well as the effect of transforming growth factor-␤ in mammary epithelial cells (39).…”
Section: Resultscontrasting
confidence: 93%
“…8D). Previous studies in fibroblasts have shown that motility-promoting concentrations of PDGF-BB promote FAK phosphorylation at Tyr-397 and the stimulated SH2-mediated binding of Src family PTKs to this site on FAK (12,36). Using a phosphospecific antibody directed to the FAK Tyr-397 site, stable FRNK expression but not FRNK L1034S resulted in the reduced phosphorylation of FAK Tyr-397 after PDGF-BB stimulation of SMCs (Fig.…”
Section: Frnk Blocks the Formation Of A Complex Between Fak And Pdgfrmentioning
confidence: 76%
“…Samples were analysed by immunoblotting. For the FAK-Src and FAK-p85 co-immunoprecipotation experiments, cells were lysed in RIPA lysis buffer containing 50 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1% Triton X-100, 0.1% sodium dodecyl sulfate (SDS), 0.5% sodium dehoxycolate and protease inhibitors as reported previously (Salazar and Rozengurt, 1999). Cell lysates were incubated overnight at 41C with the appropriate primary antibodies and subsequently for 2 h with protein G-agarose or protein A-agarose (both from Invitrogen).…”
Section: Immunoprecipitationmentioning
confidence: 99%